GABAergic modulation in central sensitization in humans: a randomized placebo-controlled pharmacokinetic–pharmacodynamic study comparing clobazam with clonazepam in healthy volunteers. Issue 3 (March 2015) - Besson, Marie; Matthey, Alain; Daali, Youssef; Poncet, Antoine; Vuillemier, Pascal; Curatolo, Michele; Zeilhofer, Hanns Ulrich; Desmeules, Jules
Abstract : Abstract: Positive allosteric modulators of GABAA receptors (GAMs) acting at specific subtypes of GABAA receptors effectively restore compromised spinal pain control in rodents. Studies addressing a similar antihyperalgesic effect in humans are sparse and are hampered by sedative effects of nonselective GAMs available for use in humans. We present results from a randomized controlled double-blind crossover study in 25 healthy volunteers, which addressed potential antihyperalgesic actions of clobazam (CBZ) and clonazepam (CLN) at mildly sedating equianticonvulsive doses. Clobazam was chosen because of its relatively low sedative properties and CLN because of its use in neuropathic pain. Tolterodine (TLT) was used as an active placebo. The primary outcome parameter was a change in the area of cutaneous UVB irradiation–induced secondary hyperalgesia (ASH), which was monitored for 8 hours after drug application. Sedative effects were assessed in parallel to antihyperalgesia. Compared with TLT, recovery from hyperalgesia was significantly faster in the CBZ and CLN groups ( P = 0.009). At the time point of maximum effect, the rate of recovery from hyperalgesia was accelerated by CBZ and CLN, relative to placebo by 15.7% (95% confidence interval [CI] 0.8-30.5), P = 0.040, and 28.6% (95% CI 4.5-52.6), P = 0.022, respectively. Active compounds induced stronger sedation than placebo, but these differences disappeared 8 hours after drug application. We demonstrate here that GAMs effectively reduce central sensitization in healthy volunteers. These results provide proof-of-principle evidence supporting efficacy of GAMs as antihyperalgesic agents in humans and should stimulate further research on compounds with improved subtype specificity. Abstract : This proof-of-concept study demonstrates that facilitation of GABAergic synaptic transmission has a statistically significant effect on experimental secondary hyperalgesia in humans.